Las ideas del alumnado sobre el concepto de célula al finalizar la Educación General Básica - Caballer Senabre, Mª Jesús; Giménez, I. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This work presents research on children's ideas concerning cells. The concept of the cell is studied from 13 years onwards and is developed in many biology textbooks at this level. The autor's hypothesis is that the concept of the cell is very complex and that it is not possible to understand the functioning as a living organism, nor is it possible to understand the functioning of its organs until a basic knowlege of biochemistry, respiration and photosyntesis is acquired.